PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PROMOSI SOCIAL COMMERCE USAHA BRO.DO - Thallita Affifah Nugroho; Farah Citra Azzahra (Jurnal Pustaka Komunikasi, 2022)
Brodo is an industry that runs in the fashion sector and has been running for 11 years. In this modern era, Brodo uses social media as a means of expanding information about the types of products offered by Brodo, namely the features on Brodo's Instagram are used as well as possible. The purpose of this study was to find out how the role of Instagram as a publication media for Brodo. The theory used in this research is Promotion and Marketing Mix 7P. The method used in this study is a qualitative descriptive method. The findings obtained in this study are the maximum utilization results in making Instagram as Brodo's publication media. Supported by the activities that Brodo carries out on its Instagram, consistently and innovatively uploading Brodo content on Instagram and conveying it well by the public. In this study it was found that Brodo has used Instagram as a publication medium and in its implementation Brodo is more focused on providing stories and information through the Brodo.do Instagram platform.